Lipid-lowering therapy use in primary and secondary care in Central and Eastern Europe: DA VINCI observational study. (October 2021) - Vrablik, Michal; Seifert, Bohumil; Parkhomenko, Alexander; Banach, Maciej; Jóźwiak, Jacek J.; Kiss, Robert Gabor; Gaita, Dan; Rašlová, Katarina; Zachlederova, Marie; Bray, Sarah; Ray, Kausik K.
Abstract: Background and aims: Central and Eastern Europe (CEE) is a largely understudied region, despite having the highest cardiovascular disease mortality in Europe. This analysis aimed to assess the proportion of patients in CEE who achieved their LDL-C goals based on individual cardiovascular risk recommended by the 2016 and 2019 European Society of Cardiology (ESC)/European Atherosclerosis Society (EAS) guidelines. Methods: The DA VINCI study was a cross-sectional observational study of primary and secondary prevention patients receiving lipid-lowering therapy across Europe between June 2017 and November 2018. Results: In total, 2154 patients were enrolled from the Czech Republic (n = 509), Hungary (n = 319), Poland (n = 460), Romania (n = 259), Slovakia (n = 123) and Ukraine (n = 484). At LDL-C measurement, most patients were on either moderate- or high-intensity statin monotherapy (53% and 32%, respectively). Despite this, only 44% of patients achieved risk-based LDL-C goals recommended by the 2016 ESC/EAS guidelines, ranging from 21% in Ukraine to 50% in Hungary and Romania. Only 24% of patients overall achieved the risk-based LDL-C goals recommended by the 2019 ESC/EAS guidelines, ranging from 11% in Ukraine to 32% in Poland. Conclusions: Among patients receiving lipid-lowering therapy, more than half did not achieve their 2016 LDL-C goals. In one of the first comparative analyses evaluating 2019 risk-based goal attainment among countries in CEE, three-quarters of patients did not meet their 2019 LDL-C goals, highlighting a significant gap between guidelines and clinical practice for lipid management in CEE. Graphical abstract: Image 1 Highlights: This study presents data on lipid-lowering therapy use and the burden of dyslipidaemia in Central Eastern Europe, an understudied population. Among patients receiving lipid-lowering therapy, more than half did not achieve their LDL-C goals set by the 2016 EAS/ESC guidelines. In one of the first analyses evaluating 2019 LDL-C goal attainment in CEE; most patients did not achieve their goals. Goal attainment differed between CEE countries, showing a greater burden of dyslipidaemia in some countries than others. A call to action is needed to drive change in clinical practices for lipid management in CEE.